Effects of Photodeposited Gold vs Platinum Nanoparticles on N,F-Doped TiO2 Photoactivity: A Time-Resolved Photoluminescence Investigation - Dozzi, Maria Vittoria; Candeo, Alessia; Marra, Gianluigi; D’Andrea, Cosimo; Valentini, Gianluca; Selli, Elena (Journal of physical chemistry. C, 2018)
The time-resolved photoluminescence (PL) in the nanosecond time scale of TiO2 materials undoped or codoped with nitrogen and fluorine (N,F-doping) and modified by noble metals (NM, i.e. Au or Pt) nanoparticles (NPs) photodeposition has been systematically investigated in relation to their photocatalytic activity in hydrogen production. The main aim of the study is to elucidate the origin of the NM-dependent synergistic effects in photoactivity produced by N,F-doping of TiO2 and NM NPs deposition on the oxide surface. While TiO2 doping with fluorine and nitrogen introduces new stabilized luminescent defective trap states below the conduction band revealed by long-living PL components, the presence of NM NPs on the TiO2 surface produces a PL intensity suppression, which is more relevant for Au- rather than for Pt-NPs containing materials. Time-resolved PL analysis indicates that the electron transfer occurring at the TiO2/metal interface is affected by both the defective structure of anatase N,F-doped TiO2 and the type of NM (Au or Pt). In particular, Au rather than Pt NPs appear to strongly interact with the charge carriers trapped at surface defect sites, gold NPs being expected to preferentially grow on such sites during photodeposition. Furthermore, plasmonic gold NPs excitation upon PL light absorption is evidenced by the PL spectral shape variation observed only in the case of Au/TiO2. Thus, the larger synergistic effect on photocatalytic hydrogen production observed upon Au NPs photodeposition on N,F-doped TiO2 results from the opening of a new efficient electron transfer path from luminescent defective trap states on doped TiO2 to Au NPs, where proton reduction occurs.